Arca Buddha Bukit Siguntang Sebagai Simbol Keagamaan Sriwijaya - Larasatih, Jeny Latifah; Hudaidah, Hudaidah (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Siguntang Hill is a historical site that has important value in the history of the Srivijaya Kingdom, a maritime kingdom that flourished in the 7th to 13th centuries AD. One of the significant archaeological findings from this site is the Buddha statue, which reflects the influence of Mahayana Buddhism in the region. This study aims to analyze the meaning and function of the Buddha statue on Siguntang Hill as a religious symbol of Srivijaya. The research methods used include literature study, iconographic analysis, and a study of the historical and religious context of Srivijaya. The results of the study show that the Buddha statue from Siguntang Hill not only functions as an object of worship, but also as a symbol of the legitimacy of Srivijaya's power which is closely related to Buddhism. The existence of this statue indicates that Siguntang Hill was an important spiritual center, playing a role in the spread of Buddhism and strengthening Srivijaya's identity as an influential Buddhist kingdom in Southeast Asia.